Shell of sound production device, sound production device and electronic equipment
A composite shell made of carbon fiber and alloy material with polypropylene and polyamide addresses the issues of low welding strength and high density in PA66 shells, achieving improved bonding and lightweight design through enhanced ultrasonic welding.
Patent Information
- Application Number
- CN202411214804.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-20
AI Technical Summary
Existing sound module shells made of PA66 (nylon) + fiber material suffer from low welding strength due to high melting enthalpy, leading to cold welds and poor air tightness, and have a high density that does not meet lightweight design requirements.
A shell composed of a composite material with a mass ratio of carbon fiber to alloy material ranging from 0.12-0.69, where the alloy material consists of polypropylene and polyamide, optionally with a compatibilizer, is used for ultrasonic welding, enhancing bonding strength and airtightness while reducing density.
The composite material improves welding firmness, airtightness, and bonding strength, while maintaining a lightweight design by utilizing carbon fiber for high strength and modulus, and polyamide for improved temperature resistance and surface energy.
Smart Images

Figure CN119172698A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electroacoustic conversion, and more specifically, to a shell of a sound-generating device, a sound-generating device and an electronic device. Background Art
[0002] The sound module generally includes a module shell and a sound unit disposed in the module shell. The module shell includes a module upper shell and a module lower shell. The sound unit cooperates with the module shell to define a front sound cavity and a rear sound cavity. The module shell is provided with a sound outlet hole connected to the front sound cavity. The module shell is made of metal material and / or plastic material.
[0003] In the related art, a module shell made of a composite of PA66 (nylon) + fiber material is proposed. The module shell has a high structural strength and meets the use requirements of the sound module. When the sound module is assembled, the upper shell of the module is connected to the lower shell of the module by ultrasonic welding. However, due to the high melting enthalpy of the PA66 material, the welding strength of the upper shell of the module and the lower shell of the module is low when ultrasonically welding, there are a large number of cold welds, and the air tightness of the shell is poor; and the density of the material used to prepare the module shell is relatively high, resulting in a large mass of the shell, which does not meet the lightweight design requirements of the sound module. Therefore, it is necessary to provide a new technical solution to solve the above technical problems. Summary of the invention
[0004] An object of the present invention is to provide a new technical solution for a housing of a sound-generating device.
[0005] According to a first aspect of the present invention, a shell of a sound-generating device is provided. The shell includes a first shell and a second shell, the first shell and the second shell are both provided with a welding portion, the welding portion of the first shell and the welding portion of the second shell are ultrasonically welded, the welding portion is injection-molded from a composite material consisting of carbon fiber and an alloy material, the mass ratio of the carbon fiber to the alloy material is 0.12-0.69, the alloy material includes polypropylene and polyamide, and the mass ratio of the polyamide to the polypropylene in the alloy material is 0.1-0.5.
[0006] Optionally, the alloy material further includes a compatibilizer. In the alloy material, the content of the polypropylene is 60wt%-90wt%, the content of the polyamide is 9wt%-30wt%, and the content of the compatibilizer is 1wt%-10wt%.
[0007] Optionally, the compatibilizer includes at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted polyethylene, ethylene acrylate copolymer, ethylene methacrylate copolymer, maleic anhydride grafted polystyrene, and maleic anhydride grafted EVA.
[0008] Optionally, the polyamide includes at least one of long-chain polyamide and amorphous polyamide.
[0009] Optionally, the long-chain polyamide includes at least one of PA610, PA612, PA1010, PA11, PA12, PA1212, PA1012, PA1111, PA1213, and PA1313;
[0010] And / or, the melting enthalpy of the amorphous polyamide material is ≤5 J / g.
[0011] Optionally, the alloy material further comprises hollow glass microspheres, and the distribution density of the hollow glass microspheres in the composite material is 0.45 g / cm 3 -0.75g / cm 3 .
[0012] Optionally, the carbon content of the carbon fiber is 90%-99.99%, and / or the graphitization degree R of the carbon fiber is 0.85-1.15, and / or the length of the carbon fiber is 0.1mm-1mm.
[0013] Optionally, the carbon fiber is sizing treated with a sizing agent, and the sizing agent includes at least one of a polystyrene sizing agent, a polyamide sizing agent, a polyester sizing agent, and an epoxy resin sizing agent.
[0014] Optionally, at least one of the first shell and the second shell is integrally formed as a welded portion; or
[0015] At least one of the first shell and the second shell includes a supporting portion, and the supporting portion is injection-moldedly connected to the welding portion.
[0016] Optionally, the supporting portion includes a resin material, and the resin material includes at least one of PP, PA610, PA612, PA1010, PA11, PA12, PA1212, PA1012, PA1111, PA1213, PA1313, PPA, PA4T, PA6T, PA9T, PA10T, PA12T, PA46, ABS, PET, PBT, and PC.
[0017] Optionally, the support portion further comprises a fiber material, the fiber material comprises carbon fiber and / or glass fiber, the resin material is mixed with the fiber material, and the mass ratio of the fiber material to the resin material is 0.1-0.7.
[0018] Optionally, the density of the shell is 0.9 g / cm 3 -1.25g / cm 3 ;
[0019] And / or, at least 10% of the area of the shell has a thickness of ≤0.3 mm.
[0020] Optionally, the bending modulus of the shell is 5GPa-35GPa;
[0021] And / or, the bending strength of the shell is 50MPa-350Mpa;
[0022] And / or, the heat deformation temperature of the shell is ≥120°C.
[0023] Optionally, the surface tension of the shell is ≥36 dynes / cm;
[0024] And / or, the housing has a waterproof rating of at least 1 ATM.
[0025] According to a second aspect of the present invention, a sound-generating device is provided, which includes a housing of the sound-generating device described in the present invention.
[0026] According to a third aspect of the present invention, an electronic device is provided, which includes the sound generating device of the present invention.
[0027] In an embodiment of the present invention, the welding part of the first shell and the second shell is formed by injection molding of a composite material composed of carbon fiber and alloy material. The alloy material includes polypropylene and polyamide. The melting temperature of the alloy material is low and the heat enthalpy required for melting is small, which makes ultrasonic welding easier and the welding quality is better, thereby improving the welding firmness and airtightness between the first shell and the second shell. Carbon fiber can significantly improve the strength and modulus of the composite material. In reliability verification, the phenomenon of resonance between the shell and the sound-emitting monomer is not easy to occur. The composite material has a high modulus and strength, and the connection structure formed by the two welding parts during ultrasonic welding has high strength and high yield. In addition, polyamide can also improve the problem of low surface energy of polypropylene, thereby improving the bonding force between the reinforcement part and the glue, and improving the bonding strength between the shell and other parts of the sound-emitting device.
[0028] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.
[0030] Figure 1 is an exploded view of a sound generating device according to an embodiment of the present invention.
[0031] Figure 2 is a cross-sectional view of a sound generating device according to an embodiment of the present invention.
[0032] Figure 3 is a cross-sectional view of another sound-generating device according to an embodiment of the present invention.
[0033] Figure 4 3 are frequency response curves of the sound-generating devices according to Example 1 of the present invention and Comparative Example 3.
[0034] Description of reference numerals:
[0035] 10. First shell; 111. Front sound cavity; 121. Rear sound cavity; 15. Welding part; 16. Support part; 20. Sound unit; 30. PCB; 40. Second shell. DETAILED DESCRIPTION
[0036] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.
[0037] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.
[0038] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.
[0039] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0040] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.
[0041] According to one embodiment of the present invention, a shell of a sound-generating device is provided. The shell includes a first shell 10 and a second shell 40, wherein the first shell 10 and the second shell 40 are both provided with a welding portion 15, wherein the welding portion 15 of the first shell 10 and the welding portion 15 of the second shell 40 are connected by ultrasonic welding, wherein the welding portion 15 is injection-molded from a composite material composed of carbon fiber and an alloy material, wherein the mass ratio of the carbon fiber to the alloy material is 0.12-0.69, wherein the alloy material includes polypropylene and polyamide, wherein the mass ratio of the polyamide to the polypropylene in the alloy material is 0.1-0.5.
[0042] Specifically, Figure 1-Figure 3As shown, the first shell 10 and the second shell 40 are connected together to form a accommodating cavity therein. The accommodating cavity is used to accommodate the sound unit 20 and the PCB 30. The sound unit 20 is connected to the PCB 30. The PCB 30 is connected to the external circuit. A welding portion 15 is provided at the edge of the first shell 10 and the second shell 40. The welding portion 15 is formed by injection molding of a composite material. When connecting, the two welding portions 15 are arranged opposite to each other, and the two welding portions 15 are melted by ultrasonic welding, and the two welding portions 15 are bonded to each other. After curing, the two welding portions 15 are connected together.
[0043] In this embodiment, the composite material includes carbon fiber and alloy material mixed together. The alloy material is formed by blending a variety of polymers. The alloy material can have the advantages of a variety of polymers, such as low melting temperature, high strength, high modulus, etc. The density of polypropylene is relatively small, but the melting point is relatively low and the temperature resistance is relatively poor; the melting point of polyamide is relatively high and the temperature resistance is good, but it is easy to cause problems such as cold welding during ultrasonic welding, and the welding yield is low. Polyamide can significantly improve the temperature resistance of polypropylene. The alloy material includes polypropylene and polyamide blended together. The melting temperature of the alloy material is low, and the thermal enthalpy required for melting is small. In ultrasonic welding, the alloy material is easy to melt, so that the welding interface bonding strength of the two welding parts 15 is high. The density of the alloy material is small, so that the alloy material meets the demand for lightweight shell. In addition, the surface energy of the alloy material is significantly improved compared to polypropylene, which enables the alloy material to significantly improve the bonding strength with the diaphragm glue (for example, UV glue).
[0044] Wherein, the mass ratio of the polyamide to the polypropylene is 0.1-0.5. It should be noted that, in the alloy material, when the mass ratio of polyamide to polypropylene is less than 0.1, the temperature resistance of polyamide to polypropylene is improved less; when the mass ratio of polyamide to polypropylene is greater than 0.5, the high melting point of polyamide will cause the ultrasonic welding of the alloy material to be difficult, resulting in problems such as cold welding, and the welding yield rate is reduced. In this embodiment, the mass ratio of the polyamide to the polypropylene is 0.1-0.5. Within this range, the melting point of the alloy material is relatively high, so that the shell can be used for a long time at high temperature without deformation, and the alloy material can be melted at a lower ultrasonic energy when the shell is ultrasonically welded, avoiding the occurrence of cold welding, so that the ultrasonic welding of the shell has a high welding strength. In addition, compared with polypropylene, the surface energy of the alloy material is significantly improved, so that the bonding force between the shell and the diaphragm glue is higher, and the diaphragm and the shell are firmly bonded. The density of the alloy material is small, which meets the lightweight requirements of the shell. Optionally, the mass ratio of the polyamide to the polypropylene is 0.1, 0.2, 0.3, 0.4, 0.5, etc. With the above values, the alloy material can meet the requirements of long-term use of the shell at high temperature, the requirements of ultrasonic welding, and the requirements of low density and high surface energy.
[0045] Carbon fiber is a high-performance fiber material with high strength and high modulus, which is made from organic fibers (such as polyacrylonitrile, viscose fiber or asphalt) through carbonization and other processes. The density of carbon fiber is lower than that of glass fiber, and the carbon fiber reinforced shell structure strength effect is better. Under the condition of meeting the shell strength and modulus requirements, the amount of carbon fiber added to the composite material is lower, which is conducive to achieving lightweight shell.
[0046] In addition, the mass ratio of the carbon fiber to the alloy material is 0.12-0.69. When the mass ratio of the carbon fiber to the alloy material is greater than 0.69, due to the high distribution density of the carbon fiber in the composite material, the alloy material at the welding interface of the welding portion 15 is relatively small, resulting in poor welding defects such as cold welding at the welding interface, and the welding strength and welding yield are reduced. As the mass ratio of the carbon fiber to the alloy material continues to increase, the melting index of the composite material decreases, the viscosity of the melt increases, and the glue injection becomes difficult, resulting in an increase in the proportion of products with glue shortage. The ultrasonic welding strength and welding yield of the welding portion 15 of the first shell 10 and the second shell 40 will be significantly reduced. On the contrary, when the mass ratio of the carbon fiber to the alloy material is less than 0.12, the reinforcing effect of the carbon fiber on the strength and modulus of the composite material is poor. During the reliability verification process of the sound-generating device, the shell is prone to resonance between the shell and the sound-generating monomer 20 in the intermediate frequency stage, resulting in excessive distortion of the intermediate frequency THD of the sound-generating device. When the mass ratio of the carbon fiber to the alloy material is 0.12-0.69, the melting temperature of the composite material is low, making ultrasonic welding easier, the welding of the two welding parts 15 is firm, and the strength and modulus of the shell are high. Optionally, the mass ratio of the carbon fiber to the alloy material is 0.12, 0.15, 0.20, 0.25, 0.3, 0.35, 0.4, 0.45, 0.46, 0.50, 0.55, 0.60, 0.65, 0.69, and the above values can make the melting temperature of the composite material low, ultrasonic welding is easy, and the overall modulus and structural strength of the formed shell are high.
[0047] The preparation process of the shell of the present invention may include:
[0048] (1) Preparation of composite materials. Polypropylene and polyamide are added to a twin-screw extruder from the main feed port according to a set mass ratio for melting. After the two materials are melted, carbon fiber is added from the side feed port. The carbon fiber and the mixed alloy material are sheared and mixed uniformly in the extruder, and then extruded into granules.
[0049] (2) Preparation of the shell. The granulated composite material is melted again during injection molding and then injected into a mold to form the first shell 10 and the second shell 40;
[0050] Alternatively, during injection molding, the support portion 16 is firstly formed by injection molding in a mold, and then the welding portion 15 is formed by injection molding at the edge of the support portion 16 , thereby forming the first shell 10 and the second shell 40 .
[0051] (3) Assemble the sound unit 20 and PCB 30 and other components into the accommodation cavity formed by the first shell 10 and the second shell 40. Then, align the two welding parts 15 of the first shell 10 and the second shell 40, and perform ultrasonic welding to connect the two welding parts 15 together.
[0052] It should be noted that the length-to-diameter ratio of carbon fiber is relatively large, and its ability to resist shear is not high, so it is usually necessary to add carbon fiber after the alloy material is melted. This can effectively reduce the damage of the carbon fiber during the mixing process, thereby enhancing the reinforcement effect of carbon fiber on the composite material.
[0053] In an embodiment of the present invention, the welding portion 15 of the first shell 10 and the second shell 40 is formed by injection molding of a composite material. The welding portion 15 is formed by injection molding of a composite material, and the composite material includes carbon fiber and alloy material mixed together. The melting temperature of the alloy material is low, and the heat enthalpy required for melting is small, which makes ultrasonic welding easier and the welding quality is better, thereby improving the welding firmness and airtightness between the first shell 10 and the second shell 40. Carbon fiber can significantly improve the strength and modulus of the composite material. In reliability verification, it is not easy for the shell and the sound-emitting monomer 20 to resonate. The composite material has a high modulus and strength, and the connection structure formed by the two welding portions 15 during ultrasonic welding has high strength and high yield. In addition, polyamide can also improve the problem of low surface energy of polypropylene, thereby improving the bonding force between the reinforcement and the glue, and improving the bonding strength between the shell and other parts of the sound-emitting device.
[0054] In a specific embodiment of the present invention, the alloy material further includes a compatibilizer. In the alloy material, the content of the polypropylene is 60wt%-90wt%, the content of the polyamide is 9wt%-30wt%, and the content of the compatibilizer is 1wt%-10wt%.
[0055] Generally, the compatibility of polypropylene and polyamide is poor, which makes it difficult to fully mix the two during blending to form a uniform alloy material, and the blending time is long. Compatibilizers can significantly improve the compatibility of polypropylene and polyamide, so that polypropylene and polyamide can be fully mixed to form a uniform alloy material, greatly shortening the blending time.
[0056] In addition, when the proportion of the compatibilizer in the alloy material is less than 1wt%, the compatibility of polypropylene and polyamide is not significantly improved; when the proportion of the compatibilizer in the alloy material is greater than 10wt%, the overall temperature resistance of the alloy material will be deteriorated. In this embodiment, the proportion of the compatibilizer in the alloy material is 1-10wt%. Within this range, the compatibilizer can significantly improve the compatibility of polypropylene and polyamide, and the overall temperature resistance of the alloy material is good. Optionally, the content of the compatibilizer in the alloy material is 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc. At the above values, the compatibilizer can significantly improve the compatibility of polypropylene and polyamide, and the overall temperature resistance of the alloy material is good.
[0057] In some embodiments of the present invention, the content of polyamide in the alloy material is 9wt%-30wt%. When the proportion of polyamide in the alloy material is less than 9wt%, the improvement of the temperature resistance of polyamide to polypropylene is small; when the proportion of polyamide in the alloy material is greater than 30wt%, the high melting point of polyamide will cause difficulty in ultrasonic welding of the shell, resulting in problems such as cold welding, and the welding yield of the shell is reduced. In this embodiment, the content of polyamide in the alloy material is 9wt%-30wt%. Within this range, the alloy material has good temperature resistance and moderate melting point, high ultrasonic welding strength, and high welding yield of the shell. Optionally, the content of polyamide in the alloy material is 9wt%, 10wt%, 15wt%, 20wt%, 25wt%, 28wt%, 30wt%, etc. The above values can make the alloy material have good temperature resistance and moderate melting point, high ultrasonic welding strength, and high welding yield of the shell.
[0058] The content of the compatibilizer in the alloy material is 1-10wt%. The content of the polyamide in the alloy material is 9wt%-30wt%, and correspondingly, the content of the polypropylene is 60wt%-90wt%. Within this range, the alloy material has good temperature resistance and a moderate melting point, high ultrasonic welding strength, and high welding yield of the shell.
[0059] In a specific embodiment of the present invention, the compatibilizer includes at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted polyethylene, ethylene acrylate copolymer, ethylene methacrylate copolymer, maleic anhydride grafted polystyrene, and maleic anhydride grafted EVA.
[0060] In other words, the compatibilizer is selected from any one or a mixture of maleic anhydride grafted polypropylene, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted polyethylene, ethylene acrylate copolymer, ethylene methacrylate copolymer, maleic anhydride grafted polystyrene, and maleic anhydride grafted EVA. The above compatibilizers can have good compatibility with polyamide and significantly improve the compatibility of polypropylene and polyamide.
[0061] In a specific embodiment of the present invention, the polyamide includes at least one of long-chain polyamide and amorphous polyamide.
[0062] In other words, the polyamide may be a long-chain polyamide or an amorphous polyamide; or a mixture of a long-chain polyamide and an amorphous polyamide.
[0063] Among them, the long-chain polyamide has a longer carbon chain relative to the short-chain polyamide (such as PA46, PA66, etc.), for example, the average number of carbon atoms in the structural unit of the long-chain polyamide is greater than or equal to 10. The melting temperature of the long-chain polyamide is relatively low, for example, it can reach 150°C to 220°C. During the ultrasonic welding process, the energy required for the crystallization and melting of the long-chain polyamide is low, making ultrasonic welding easier and the welding quality better, thereby improving the welding strength between the first shell 10 and the second shell 40. In addition, the welding consistency of each part of the welding portion 15 is good, and it is not easy to form defects such as cold welding and poor air tightness, which can improve the welding air tightness between the first shell 10 and the second shell 40 and improve the waterproof effect of the shell. In addition, the long-chain polyamide has the characteristics of low density, which is conducive to the lightweight design of the shell.
[0064] Amorphous polyamide is composed of irregularly arranged repeating units and is an amorphous substance. Since there is no crystalline structure in amorphous polyamide, there is no phase interface between amorphous components and crystalline components, and the phase interface will cause the dissipation of welding energy during welding, resulting in poor welding, such as cold welding, poor air tightness and the like. In the present invention, the composite material includes amorphous polyamide. Since there is no phase interface between amorphous components and crystalline components in amorphous polyamide, the ultrasonic vibration energy can be well transmitted in the material during ultrasonic welding, which is conducive to transmitting the ultrasonic vibration energy to the two welding parts 15. The two welding parts 15 are easier to melt, and the firmness of the welding of the first shell 10 and the second shell 40 is effectively improved. Since amorphous polyamide has no crystalline structure, the heat required for melting of the welding interface of the two welding parts 15 is lower, the energy required for ultrasonic welding is lower, and it is easier to weld, thereby improving the welding strength between the first shell 10 and the second shell 40. In addition, the welding consistency of each part of the welding part 15 is good, and it is not easy to form defects of cold welding and poor air tightness, which can improve the welding air tightness between the first shell 10 and the second shell 40 and improve the waterproof effect of the module shell. In addition, since amorphous polyamide has no crystalline structure, it has the characteristic of low density, which is conducive to the lightweight design of the shell.
[0065] In a specific embodiment of the present invention, the long-chain polyamide includes at least one of PA610, PA612, PA1010, PA11, PA12, PA1212, PA1012, PA1111, PA1213, and PA1313;
[0066] And / or, the melting enthalpy of the amorphous polyamide material is ≤5 J / g.
[0067] In this embodiment, the long-chain polyamides mentioned above all have a relatively low melting point and can be uniformly mixed with carbon fibers to form a composite material. During preparation, any one or more of the long-chain polyamides mentioned above can be mixed together to form a molten substance, and then the carbon fibers and the molten substance are mixed together. For example, the above materials and polypropylene are melted in an extruder, and then carbon fibers are added and mixed together to form a composite material.
[0068] The enthalpy of fusion is a physical quantity that characterizes the amount of heat consumed by a substance during the melting process. Specifically, the enthalpy of fusion is the amount of heat absorbed at constant temperature and pressure when a substance changes from a solid to a liquid. The greater the enthalpy of fusion of the amorphous polyamide, the higher the energy consumed during melting. In this embodiment, the enthalpy of fusion of the amorphous polyamide is ≤5J / g. Within this range, the composite material consumes less energy during ultrasonic welding, and the melting of the composite material is easier. Optionally, the enthalpy of fusion of the amorphous polyamide is 2J / g, 3J / g, 4J / g, 5J / g, etc. The above values all consume less energy during ultrasonic welding of the composite material, and the welding of the composite material is easier.
[0069] In a specific embodiment of the present invention, the composite material further comprises hollow glass microspheres, and the distribution density of the hollow glass microspheres in the composite material is 0.45 g / cm 3 -0.75g / cm 3 .
[0070] In this embodiment, when preparing the composite material, hollow glass microspheres and carbon fibers are added to the alloy material melt; after mixing, a composite material is finally formed. Since the hollow glass microspheres may be sheared and damaged during the mixing process, the hollow glass microspheres are added after the carbon fibers are added to minimize the shear damage of the hollow glass microspheres during the mixing process. The hollow glass microspheres can significantly reduce the density of the composite material and meet the demand for lightweight shells.
[0071] It should be noted that when the mass percentage of the hollow glass microspheres in the composite material is less than 1%, the effect of reducing the density of the composite material is not obvious; on the contrary, when the mass percentage of the hollow glass microspheres in the composite material is greater than 20%, the impact resistance of the composite material will decrease, and the shell will be easily damaged in the drop reliability test of the sound-generating device. In this embodiment, the mass percentage of the hollow glass microspheres is 1%-20%. Within this range, the density of the composite material can be effectively reduced, and the connection strength of the two welding parts 15 is high, and the shell is not easy to be damaged. Optionally, the mass percentage of the hollow glass microspheres is 1%, 2%, 4%, 6%, 9%, 10%, 12%, 13%, 14%, 16%, 17%, 18%, 19%, 20%. The above values can effectively reduce the density of the composite material, and the connection strength of the two welding parts 15 is high, and the shell is not easy to be damaged.
[0072] The distribution density of hollow glass microspheres in composite materials refers to the mass of hollow glass microspheres per unit volume of the composite material. The distribution density of hollow glass microspheres is less than 0.45 g / cm 3 When the density of the review material is reduced, the effect is not obvious; on the contrary, the distribution density of the hollow glass microspheres is greater than 0.75g / cm3 When the composite material is subjected to the impact test, the impact resistance of the composite material will be reduced. In the drop reliability test of the sound-generating device, the shell is easily damaged. In this embodiment, the distribution density of the hollow glass microspheres in the composite material is 0.45 g / cm 3 -0.75 / cm 3 Within this range, the density of the composite material can be effectively reduced, and the connection strength of the two welding parts 15 is high, and the shell is not easily damaged. Optionally, the distribution density of the hollow glass microspheres in the composite material is 0.45 g / cm 3 , 0.5g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.75g / cm 3 The above values can effectively reduce the density of the composite material and increase the connection strength of the two welding portions 15, so that the shell is not easily damaged.
[0073] In a specific embodiment of the present invention, the carbon content of the carbon fiber is 90%-99.99%.
[0074] And / or, the graphitization degree R of the carbon fiber is 0.85-1.15,
[0075] And / or, the length of the carbon fiber is 0.1 mm-1 mm.
[0076] Specifically, the lower the carbon content of the carbon fiber, the lower the modulus of the carbon fiber; conversely, the higher the carbon content of the carbon fiber, the higher the modulus of the carbon fiber. In this embodiment, the carbon content of the carbon fiber is 90%-99.99%. Within the range, under the same mass content conditions, the modulus of the composite material is high and the overall structural strength of the shell is high. Optionally, the carbon content of the carbon fiber is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, 99.99%, etc. The above values can all make the modulus of the composite material high and the overall structural strength of the shell high.
[0077] The graphitization degree R value refers to the value of 1360cm when the Raman spectrum is used to test the carbon fiber. -1 The peak intensity of 1583cm -1The ratio of peak intensity. The degree of graphitization is inversely proportional to the R value. The smaller the R value, the higher the degree of graphitization, the higher the degree of graphitization of the carbon fiber, the higher the modulus along the fiber direction, and the higher the effect of improving the modulus of the composite material. When the R value is greater than 1.15, the graphitization degree of the carbon fiber is too small, and the modulus improvement effect on the composite material is poor. When the R value is less than 0.85, the degree of graphitization of the carbon fiber is high, and the raw material requirements and processing requirements for the carbon fiber are both high, which increases the cost. In this embodiment, the graphitization degree R value of the carbon fiber is 0.85-1.15. Within this range, the modulus of the composite material is high and the cost of the carbon fiber is low, and the cost of the composite material is low. Optionally, the graphitization degree R value of the carbon fiber is 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15. The above values can all make the modulus of the composite material high and the cost low.
[0078] In addition, the length of the carbon fiber is 0.1mm-1mm. When the length of the carbon fiber is less than 0.1mm, the strength of the shell will decrease at the same carbon fiber content, resulting in damage to the shell in the drop reliability test; when the length of the carbon fiber is greater than 1mm, during the injection molding process, the shell is prone to problems such as exposed fibers and floating fibers, affecting the product yield. When the length of the carbon fiber is 0.1mm-1mm, the strength of the shell is high, and the shell is not prone to problems such as exposed fibers and floating fibers during the injection molding process, and the product yield is high. Optionally, the length of the carbon fiber is 0.1mm, 0.2mm, 0.3mm, 0.2mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, etc. The above values can all make the shell strong, and the shell is not prone to problems such as exposed fibers and floating fibers during the injection molding process.
[0079] In a specific embodiment of the present invention, the carbon content of the carbon fiber is 90%-99.99%; the graphitization degree R of the carbon fiber is 0.85-1.15. In this embodiment, the composite material has a high modulus, the overall structural strength of the shell is high and the cost is low.
[0080] In a specific embodiment of the present invention, the graphitization degree R of the carbon fiber is 0.85-1.15; the length of the carbon fiber is 0.1mm-1mm. In this embodiment, the composite material has a high modulus, the overall strength of the shell is high, the cost is low, and the shell is not prone to problems such as exposed fibers and floating fibers during the injection molding process.
[0081] In a specific embodiment of the present invention, the carbon content of the carbon fiber is 90%-99.99%; the length of the carbon fiber is 0.1mm-1mm. In this embodiment, the modulus of the composite material is high, the overall strength of the shell is high, and the shell is not prone to problems such as exposed fibers and floating fibers during the injection molding process.
[0082] In a specific embodiment of the present invention, the carbon content of the carbon fiber is 90%-99.99%; the graphitization degree R of the carbon fiber is 0.85-1.15; and the length of the carbon fiber is 0.1mm-1mm. In this embodiment, the composite material has a high modulus, the overall strength of the shell is high, the cost is low, and the shell is not prone to problems such as exposed fibers and floating fibers during the injection molding process.
[0083] In a specific embodiment of the present invention, the carbon fiber is sizing treated with a sizing agent, and the sizing agent includes at least one of a polystyrene sizing agent, a polyamide sizing agent, a polyester sizing agent, and an epoxy resin sizing agent.
[0084] In this embodiment, the surface of carbon fiber is inert, has poor compatibility with alloy materials, and has low bonding strength. In the composite material preparation process, the surface of carbon fiber needs to be surface treated to improve the compatibility of carbon fiber and long-chain polyamide. Carbon fiber is sizing treated with a sizing agent. The sizing agent includes at least one of a polystyrene sizing agent, a polyamide sizing agent, a polyester sizing agent, and an epoxy resin sizing agent. The above sizing agents can all improve the bonding strength of carbon fiber and alloy materials and improve the compatibility of carbon fiber and alloy materials.
[0085] In a specific embodiment of the present invention, at least one of the first shell 10 and the second shell 40 is integrally formed as a welded portion.
[0086] In other words, in this embodiment, the first shell 10 and / or the second shell 40 are all formed by integral injection molding of a composite material, the composite material includes a mixed alloy material and carbon fiber, the mass ratio of the carbon fiber to the alloy material is 0.12-0.69, the alloy material includes polypropylene and polyamide, and the mass ratio of the polyamide to the polypropylene in the alloy material is 0.1-0.5. As mentioned above, the shell has the characteristics of high modulus, high strength, light weight, easy ultrasonic welding, and high welding yield. For example, the first shell 10 is all formed by integral injection molding of a composite material, and a part of the structure of the second shell 40 is formed by integral injection molding of a composite material; or, a part of the structure of the first shell 10 is formed by integral injection molding of a composite material, and the second shell 40 is all formed by integral injection molding of a composite material; or, both the first shell 10 and the second shell 40 are all formed by integral injection molding of a composite material.
[0087] In a specific embodiment of the present invention, at least one of the first shell 10 and the second shell 40 further includes a support portion 16 , and the support portion 16 and the welding portion 15 are integrally injection molded.
[0088] Specifically, if Figure 1-Figure 3As shown, the first shell 10 and / or the second shell 40 are formed by double-shot molding. For example, the support portion 16 is formed in one shot, and the welding portion 15 is formed on the support portion 16 in the second shot. After curing, the support portion 16 and the welding portion 15 are connected together. In this embodiment, the support portion 16 can be processed into a set shape according to actual needs to meet the sound requirements of different sound-emitting devices. The welding portion 15 is formed at the edge of the support portion 16. The welding portion 15 of the first shell 10 and the second shell 40 is used for ultrasonic welding to connect and form the shell. In this setting, different parts of the first shell 10 and / or the second shell 40 are made of different materials according to different functions, and the different materials are molded by integral injection molding. The processing technology of the first shell 10 and / or the second shell 40 is simple and the structural strength is high.
[0089] In a specific embodiment of the present invention, the supporting portion 16 includes a resin material, and the resin material includes at least one of PP, PA610, PA612, PA1010, PA11, PA12, PA1212, PA1012, PA1111, PA1213, PA1313, PPA, PA4T, PA6T, PA9T, PA10T, PA12T, PA46, ABS, PET, PBT, and PC.
[0090] When preparing the support part 16, any one of the above materials can be selected, or at least two of the above materials can be mixed together. The above materials can be processed into a set structure according to the sound generation requirements of the sound generation device.
[0091] In a specific embodiment of the present invention, the support portion 16 further comprises a fiber material, the fiber material comprises carbon fiber and / or glass fiber, the resin material is mixed with the fiber material, and the mass ratio of the fiber material to the resin material is 0.1-0.7.
[0092] In this embodiment, the fiber material is, for example, carbon fiber and / or glass fiber. The resin material and the fiber material are mixed together to form a composite material, and the fiber material can significantly improve the modulus and strength of the composite material. When the mass ratio of the fiber material to the resin material is less than 0.1, the fiber material has a small improvement on the modulus and strength of the composite material; conversely, when the mass ratio of the fiber material to the resin material is greater than 0.7, the density of the composite material formed is large and does not meet the requirements of lightweight shell. In this embodiment, the mass ratio of the fiber material to the resin material is 0.1-0.7. Within the range, the composite material has both high strength and modulus and the mass of the shell formed is light. Optionally, the mass ratio of the fiber material to the resin material is 0.1, 0.15, 0.2, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, etc., and the above values all make the composite material have both high strength and modulus and the mass of the shell formed is light.
[0093] In a specific embodiment of the present invention, the density of the shell is 0.9 g / cm 3 -1.25g / cm 3 ;
[0094] And / or, at least 10% of the area of the shell has a thickness of ≤0.3 mm.
[0095] Specifically, in this embodiment, since the shell contains an alloy material composed of polyamide and polypropylene, the density of polyamide and polypropylene is relatively small, so that the density of the alloy material is relatively small, and thus the overall density of the shell is 0.9 g / cm 3 -1.25g / cm 3 Within this range, at the same volume, the shell has a smaller mass and sufficient modulus and strength, meeting the requirement of lightweight shell. Optionally, the density of the shell is 0.9g / cm 3 , 1.0g / cm 3 , 1.10g / cm 3 , 1.20g / cm 3 , 1.25g / cm 3 The above values can make the shell light and have sufficient modulus and strength.
[0096] The thickness of at least 10% of the area of the shell is ≤0.3mm. In other words, the thickness of at least 10% of the surface area of the shell is ≤0.3m. For example, the shell includes a top wall and a side wall, and the area with a thickness of ≤0.3m is located on the top wall and / or the side wall; or the shell is a sheet structure, and the area with a thickness of ≤0.3m is located at least partially in the sheet structure. Optionally, the shell is made of injection molding of a composite material. Since the composite material has a high modulus and strength, the shell can be made thinner at least in part, thereby increasing the volume of the internal accommodating cavity of the shell, and then increasing the volume of the sound cavity of the sound-emitting device, thereby improving the sound effect of the sound-emitting device.
[0097] In a specific embodiment of the present invention, along the vibration direction of the vibration system of the sound-emitting unit 20, the thickness of at least part of the shell opposite to the sound-emitting unit 20 is ≤0.3mm. This arrangement allows the shell to have a larger space in the vibration direction of the vibration system, allowing the vibration amplitude of the sound-emitting unit 20 to be larger, effectively improving the sound effect. Optionally, the thickness of the shell is 0.1mm, 0.15mm, 0.2mm, 0.25mm, 0.3mm, etc., and the above values can all make the space inside the shell larger.
[0098] In addition, in order to make the space of the front sound cavity and / or the rear sound cavity larger, the shell of the prior art usually sets a steel sheet in the vibration direction of the vibration system of the shell to reduce the thickness. In the present invention, since the modulus and strength of the composite material are large enough, the part of the shell in the vibration direction of the vibration system can be made thinner, for example, the thickness is ≤0.3mm, thereby increasing the space of the front sound cavity and / or the rear sound cavity. This method does not need to set a steel sheet, and the shell can be integrally formed by injection molding, which makes the preparation process of the shell simpler. Moreover, the shell in the present invention is a uniform overall structure with good structural stability, and there will be no phenomenon that the structural strength and acoustic performance are affected by cracks between the steel sheet and the shell.
[0099] In a specific embodiment of the present invention, the bending modulus of the shell is 5 GPa-35 GPa.
[0100] The bending modulus reflects the ability of a material to resist deformation when subjected to a bending load. If the bending modulus of the shell is too low, for example, less than 5GPa, the shell is prone to local vibration, which is easy to resonate with the vibration of the sound-emitting monomer 20, resulting in poor sounding effect of the sound-emitting device; if the bending modulus of the shell is too high, for example, greater than 35GPa, the processing difficulty of the shell will increase and the product yield will decrease. For example, when a shell is prepared using a composite material, it is necessary to increase the amount of carbon fiber added, for example, the mass ratio of carbon fiber to alloy material is greater than 0.69, which will cause the viscosity of the alloy material melt to be too large, and it is easy to expose the fiber and lack of glue during the injection molding process. In this embodiment, the bending modulus of the shell is 5GPa-35Gpa. Within this range, it can not only avoid the resonance between the shell and the sound-emitting monomer 20, but also reduce the processing difficulty of the shell, reduce shell defects, and improve product yield. Optionally, the bending modulus of the shell is 5GPa, 10GPa, 15GPa, 20GPa, 25GPa, 30GPa, 35GPa. The above values can avoid resonance between the shell and the sound-emitting unit 20 and reduce the difficulty of processing the shell, thereby improving the product yield.
[0101] In a specific embodiment of the present invention, the bending strength of the shell is 50MPa-350Mpa.
[0102] Bending strength is the maximum normal stress that a material can withstand when it reaches a specified deflection or breaks under a bending load. When the bending strength of the shell is lower than 50MPa, the shell is prone to deformation or even fracture when impacted; when the bending strength is higher than 350MPa, the shell has poor fluidity during injection molding and is difficult to process. In this embodiment, the bending strength of the shell is 50MPa-350Mpa. Within this range, the shell is not easily deformed when impacted, and the shell has low processing difficulty and high product yield. Optionally, the bending strength of the shell is 50MPa, 100MPa, 200MPa, 300MPa, 350Mpa, etc. The above values all make the shell have excellent impact resistance and low processing difficulty, and high product yield.
[0103] In a specific embodiment of the present invention, the thermal deformation temperature of the shell is ≥120°C.
[0104] The heat deformation temperature reflects the ability of the material to resist deformation under heat and load conditions. The higher the heat deformation temperature of the shell, the more it indicates that the shell can maintain structural stability under higher conditions. In this embodiment, the heat deformation temperature of the shell is ≥120°C, so that the shell has strong high temperature resistance and is not easy to deform during high temperature and high humidity reliability and high power reliability verification. Optionally, the heat deformation temperature of the shell is 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 200°C, etc. The above values all make the shell have strong high temperature resistance and is not easy to deform during high temperature and high humidity reliability and high power reliability verification.
[0105] In a specific embodiment of the present invention, the bending modulus of the shell is 5 GPa-35 Gpa; and / or the bending strength of the shell is 50 MPa-350 MPa; and / or the thermal deformation temperature of the shell is ≥120°C.
[0106] In other words, the performance of the shell at least meets the above two conditions, which significantly improves the shell's anti-deformation ability and high temperature resistance and reduces the processing difficulty.
[0107] In a specific embodiment of the present invention, the surface tension of the shell is ≥36 dynes / cm;
[0108] And / or, the housing has a waterproof rating of at least 1 ATM.
[0109] In this embodiment, the surface tension of the shell is ≥36 dynes / cm. Dynes / cm is a unit of force, which is used to characterize the magnitude of the surface tension of the material, that is, the magnitude of the tension borne by the liquid surface per centimeter of length. When the surface tension of the shell is less than 36 dynes / cm, after the diaphragm glue is applied to the shell, due to the small surface tension of the shell, the wetting effect of the diaphragm glue on the shell surface is poor, and the adhesion between the diaphragm glue and the shell is small. In this embodiment, the surface tension of the shell is ≥36 dynes / cm, which can significantly improve the wetting effect of the diaphragm glue on the shell surface, so that the diaphragm glue is firmly bonded to the shell, and then the diaphragm can be firmly bonded to the shell. Optionally, the surface tension of the shell is 36 dynes / cm, 38 dynes / cm, 40 dynes / cm, 45 dynes / cm, 50 dynes / cm, etc., and the above values can make the diaphragm firmly bonded to the shell.
[0110] The welding portion 15 of the first shell 10 and the welding portion 15 of the second shell 40 are connected by ultrasonic welding. The welding portion 15 is formed by injection molding of a composite material. The composite material includes carbon fiber and alloy material mixed together. The alloy material includes polypropylene and polyamide. The mass ratio of the polyamide to the polypropylene in the alloy material is 0.1-0.5. In this embodiment, since the melting temperature of the alloy material is low, the heat required for melting the welding interface of the two welding portions 15 is lower, the energy of ultrasonic welding can be lower, it is easier to weld, and it is not easy to have problems such as cold welding and air gap. In addition, the mass ratio of the carbon fiber to the alloy material is 0.12-0.69, which significantly improves the strength and modulus of the welding portion 15. In the above manner, the shell will not deform or leak when the water pressure is at least 10 meters deep.
[0111] According to a second embodiment of the present invention, a sound-generating device is provided, which includes the housing of the sound-generating device described in the present invention.
[0112] like Figure 1-Figure 3 As shown, the sound-emitting device of the present invention includes a shell, a sound-emitting unit 20 and a PCB30. The shell includes a first shell 10 and a second shell 40. The first shell 10 and the second shell 40 are connected together to form a accommodating cavity therein. The accommodating cavity is used to accommodate the sound-emitting unit 20 and at least part of the PCB30. A front sound cavity 111 is formed between the first shell 10 and the sound-emitting unit 20. The front sound cavity 111 has a sound outlet hole. A rear sound cavity 121 is formed between the second shell 40 and the sound-emitting unit 20. The sound-emitting unit 20 is connected to the PCB30. The PCB30 is connected to an external circuit. The edges of the first shell 10 and the second shell 40 are both provided with a welding portion 15. The welding portion 15 is formed by injection molding of a composite material containing carbon fiber and an alloy material. The welding portions 15 of the first shell 10 and the second shell 40 are connected together by ultrasonic welding.
[0113] The sound-generating device has the characteristics of high structural strength, good high temperature resistance and good sound-generating effect.
[0114] According to a third embodiment of the present invention, an electronic device is provided. The electronic device includes the sound-generating device of the present invention. The electronic device has the characteristic of good durability. Optionally, the electronic device is a computer, a mobile phone, a watch, a television, a speaker, an AR device, a VR device, etc.
[0115] The shell of the sound-generating device and the sound-generating device according to the embodiment of the present invention are described in detail below in combination with specific embodiments and comparative examples. It is worth noting that the following description is only exemplary and not a specific limitation to the present invention.
[0116] Comparative Example 1
[0117] A shell is formed by injection molding using 70 wt % of PC material and 30 wt % of glass fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0118] Comparative Example 2
[0119] A shell is formed by injection molding of 80 wt % of PA66 material and 20 wt % of glass fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0120] Comparative Example 3
[0121] A shell is formed by injection molding using 80 wt % of PP material and 20 wt % of glass fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0122] Comparative Example 4
[0123] A shell is formed by injection molding using 90 wt % of PP material and 10 wt % of glass fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0124] Example 1
[0125] A shell is formed by injection molding using 90wt% of alloy material (wherein the mass ratio of PA12 to PP is 0.3) and 10wt% of carbon fiber, and the obtained shell is assembled with a sound-generating monomer 20 to obtain a sound-generating module.
[0126] Example 2
[0127] A shell is formed by injection molding using 80wt% of alloy material (wherein the mass ratio of PA12 to PP is 0.3) and 20wt% of carbon fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0128] Example 3
[0129] A shell is formed by injection molding using 70wt% of alloy material (wherein the mass ratio of PA12 to PP is 0.3) and 30wt% of carbon fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0130] Example 4
[0131] A shell is formed by injection molding using 60wt% of alloy material (wherein the mass ratio of PA12 to PP is 0.3) and 40wt% of carbon fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0132] Example 5
[0133] A shell is formed by injection molding using 80wt% of alloy material (wherein the mass ratio of PA1010 to PP is 0.2) and 20wt% of carbon fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0134] Example 6
[0135] A shell is formed by injection molding using 70wt% of alloy material (wherein the mass ratio of PA11 to PP is 0.3) and 30wt% of carbon fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0136] Example 7
[0137] A shell is formed by injection molding using 60wt% of alloy material (wherein the mass ratio of PA1012 to PP is 0.15) and 40wt% of carbon fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0138] Example 8
[0139] A shell is formed by injection molding using 80wt% of alloy material (wherein the mass ratio of PA612 to PP is 0.2) and 20wt% of carbon fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0140] Example 9
[0141] A shell is formed by injection molding using 80 wt % of alloy material (wherein the mass ratio of amorphous polyamide to PP is 0.2) and 20 wt % of carbon fiber, and the shell is assembled with a sound-generating monomer 20 to obtain a sound-generating device.
[0142] It should be noted that the outer dimensions of the shells in the comparative examples and the embodiments are consistent. For the convenience of comparison, the raw material proportions of comparative examples 1-4 and embodiments 1-9 are shown in Table 1.
[0143] Table 1 - Raw material ratios of the shells of the embodiments and comparative examples
[0144]
[0145] The shells of comparative examples 1-4 and the shells of embodiments 1-9 were tested for heat deformation temperature, density, bending modulus, bending strength, dyne value, UV adhesive strength and reliability, and the test results are shown in Table 2, Table 3 and Table 4.
[0146] Table 2 - Performance test comparison table of embodiments and comparative examples
[0147]
[0148]
[0149] The test conditions and standards are as follows:
[0150] (1) Flexural modulus and flexural strength test: The test is carried out in accordance with GB / T 9341-2008, the standard for determination of flexural properties of plastics.
[0151] (2) Heat deformation temperature test: The test shall be conducted in accordance with GB / T 1634.2-2004 Plastics - Determination of deformation temperature - Part 2: Plastics, hard rubber and long fiber reinforced composites.
[0152] (3) Density test method: Test in accordance with GB / T 1033.1-2008 Plastics - Determination of density of non-foamed plastics - Part 1: Immersion method, liquid pycnometer method and titration method, using the immersion method.
[0153] (4) Dyne value measurement method: The test shall be carried out in accordance with GB / T 14216-2008 Determination of wetting tension of plastic films and sheets.
[0154] (5) UV adhesive strength test: The test was conducted in accordance with GB / T 7124-2008 Adhesives - Determination of tensile shear strength.
[0155] (6) High temperature and high humidity reliability test: The sound-generating device is placed in a test environment with a temperature of 85°C and a humidity of 85% for 48 hours, and then the sound-generating device is removed to test its acoustic performance.
[0156] (7) High-power reliability test: The sound-generating device is operated at 1.1 times the rated power for 72 hours, and then its acoustic performance is tested.
[0157] (8) 10-meter waterproof verification test: The sound-generating device is placed in water at a depth of 10 meters for 30 minutes, then taken out and its acoustic performance is tested.
[0158] (9) 2-meter drop reliability test: The sound-generating device is placed at a height of 2 meters and dropped to the ground to cause a collision. The integrity of the shell of the sound-generating device is then observed and its acoustic performance is tested.
[0159] As can be seen from Table 2, the heat deformation temperature of the shell of Examples 1-9 and the heat deformation temperature of the shell of Comparative Examples 1-3 are both ≥120°C. The shell of Comparative Example 4 contains PP material. The heat deformation temperature of PP material is low, and the mass percentage of PP material is high, reaching 90%, so that the heat deformation temperature of the shell of Example 4 is low. The bending strength of the shell of Examples 1-9 and the bending strength of the shell of Comparative Examples 1-4 are both between 50MPa-350Mpa. The bending modulus of the shell of Examples 1-9 and the bending modulus of the shell of Comparative Examples 1-2 are both between 5GPa-35Gpa. The dyne value of the shell of Examples 1-9 and the dyne value of the shell of Comparative Examples 1-2 are both ≥36dyn / cm, and the UV adhesive bonding force is high. The shells of Comparative Examples 3-4 all contain PP material. The modulus of PP material is low, and the reinforcement effect of glass fiber on PP material is poor, resulting in a low bending modulus of the shell of Comparative Examples 3-4. In addition, the molecular polarity of the PP material is low and the surface energy is low, so that the dyne value of the shell of Comparative Example 3-4 is small, the UV glue does not wet the surface of the shell of Comparative Example 3-4 sufficiently, and the UV glue has low bonding strength.
[0160] In addition, the density of the shells of Examples 1-9 and Comparative Examples 3-4 is ≤1.13 g / cm 3 The density meets the requirement of lightweight shell. The shell of comparative example 1 contains PC material, the density of PC material is high, and the mass percentage of PC material in the shell of comparative example 1 is high, reaching 70%, so that the density of the shell of comparative example 1 is ≥1.33g / cm 3 The density does not meet the requirement of lightweight shell. The shell of comparative example 2 contains PA66 material, which has high density, and the mass percentage of A66 material in the shell of comparative example 2 is relatively high, reaching 80%, so that the density of the shell of comparative example 2 is ≥1.33g / cm 3 , this density does not meet the requirement of lightweight shell.
[0161] It can be seen that the shells of Examples 1-9 are formed by injection molding of a composite material, and the composite material includes mixed carbon fiber and alloy material, the mass ratio of the carbon fiber to the alloy material is 0.12-0.69, and the alloy material includes polypropylene and polyamide, and the mass ratio of the polyamide to the polypropylene in the alloy material is 0.1-0.5. The melting temperature of the alloy material is low, the shell is easy to melt, and the welding of the shell is more secure. The heat deformation temperature, bending modulus, and bending strength of the shells of Examples 1-9 are all high, indicating that the structural strength of the shell is high, the strength drop is small during high-temperature operation, and the structural stability is strong. The density of the shells of Examples 1-9 is relatively small, which meets the lightweight requirements of the shell. The dyne value and UV glue bonding force of the shells of Examples 1-9 are both high. When bonding with the diaphragm, the UV glue can effectively infiltrate the shell, thereby making the bonding between the diaphragm and the shell more secure.
[0162] Although some properties of the shells of Comparative Examples 1-4, such as the bending modulus, bending strength, heat deformation temperature, dyne value, UV adhesive bonding force of the shells of Comparative Examples 1-2, the heat deformation temperature, density, bending strength of the shells of Comparative Example 3, and the density and bending strength of the shells of Comparative Example 4, meet the requirements, the density of the shells of Comparative Examples 1-2 is too large and does not meet the requirements of lightweight shells; the bending modulus of the shells of Comparative Examples 3-4 is low, and the shells are prone to vibration locally, which is easy to resonate with the vibration of the sound-emitting monomer 20, resulting in poor sound effects of the sound-emitting device, and the shells of Comparative Examples 3-4 have low dyne values and UV adhesive bonding force. When bonding with the diaphragm, the UV adhesive cannot effectively infiltrate the shell, so that the bonding force between the diaphragm and the shell is small, and the diaphragm is easy to fall off. The heat deformation temperature of the shell of Comparative Example 4 is low, which makes the shell poor in high temperature resistance and easy to deform when working at high temperatures.
[0163] In addition to the above tests, the process performance of the shells of Examples 1-9 and Comparative Examples 1-4 was also tested, as shown in Tables 3 and Figure 4 .
[0164] Table 3 - Comparison of process performance tests of the shells of the embodiment and the comparative example
[0165]
[0166] It can be seen from Table 3 that the yield of the injection molding process of the shells of Examples 1-9 and Comparative Examples 1-4 is relatively high, and the yield of the injection molding process reaches 100%.
[0167] The ultrasonic welding yield of the shells of Examples 1-9 reached 100%. This shows that since the shells of Examples 1-9 use composite materials, the composite materials use alloy materials, and the melting temperature of the alloy materials is low, the ultrasonic welding of the first shell 10 and the second shell 40 is easier, and it is not easy to form defects such as cold welding and poor air tightness. The shell of Comparative Example 1 uses amorphous PC and glass fiber composite materials, which have a low melting temperature, so the ultrasonic welding yield is high.
[0168] The shell of comparative example 2 is made of a composite material of PA66 and glass fiber. The melting point of PA66 material reaches 255°C. During ultrasonic welding, PA66 is not easy to melt and easily forms bubbles and gaps, resulting in a low welding yield.
[0169] Table 4 - Comparison of reliability tests of the sound-generating devices of the embodiments and comparative examples
[0170] name High temperature and high humidity reliability High power reliability 10m waterproof verification 2m drop reliability Comparative Example 1 OK OK OK OK Comparative Example 2 NG OK NG NG Comparative Example 3 NG NG NG NG Comparative Example 4 NG NG NG NG Example 1 OK OK OK OK Example 2 OK OK OK OK Example 3 OK OK OK OK Example 4 OK OK OK OK Example 5 OK OK OK OK Example 6 OK OK OK OK Example 7 OK OK OK OK Example 8 OK OK OK OK
[0171] Table 4 is a reliability test comparison table of the embodiments and comparative examples. As can be seen from Table 4, the housings of embodiments 1-9 and the housing of comparative example 1 have passed the tests of high temperature and high humidity reliability, high power reliability, 10m waterproof verification, and 2m drop reliability.
[0172] Since the shell of Comparative Example 2 is made of PA66 and glass fiber composite material, PA66 has high water absorption characteristics and therefore failed the high temperature and high humidity reliability test; and after absorbing a large amount of water, the shell will be deformed, and welding defects are prone to occur in the welding parts of the shell; in addition, the melting point of PA66 material reaches 255°C. During the ultrasonic welding process, PA66 is not easy to melt and is prone to forming bubbles and voids, resulting in a low welding yield. During the 10m waterproof verification process, the shell of Comparative Example 2 cracked and failed the test; during the 2m drop reliability test, the shell of Comparative Example 2 suffered from impact cracking and failed the test.
[0173] The shell of comparative example 3 uses PP material and glass fiber composite material. The dyne value of the PP material surface is too low, resulting in insufficient UV adhesive strength and insufficient adhesion between the diaphragm and the shell. Therefore, it failed the high temperature and high humidity reliability test, high power reliability test, 10m waterproof verification test, and 2m drop reliability test.
[0174] The shell of Comparative Example 4 uses a composite material of PP material and glass fiber. The dyne value of the PP material surface is too low, resulting in insufficient UV adhesive strength. In addition, compared with the shell of Comparative Example 3, the PP material mass ratio of the shell of Comparative Example 4 is higher, and the glass fiber mass ratio is lower, resulting in insufficient rigidity of the shell of Comparative Example 4, insufficient adhesion between the diaphragm and the shell, and failed the high temperature and high humidity reliability test, high power reliability test, 10m waterproof verification test, and 2m drop reliability test.
[0175] Figure 4 : is the frequency response curve of the sound-generating device according to Example 1 of the present invention and Comparative Example 3. Wherein, the horizontal axis is the frequency, unit: Hz; the vertical axis is the response, unit: dB; a is the frequency response curve of the sound-generating device of Example 1; b is the frequency response curve of the sound-generating device of Comparative Example 3. Figure 4 It can be seen that the response of curve a increases with the increase of frequency in the range of 100Hz-1000Hz; after 1000Hz, as the frequency increases, the response remains above 90dB. Curve b basically coincides with curve a before 10000Hz, but after exceeding 10000Hz, a downward peak appears, which indicates that due to the insufficient bending modulus of the shell of comparative example 3, the rigidity of the shell is insufficient, and the shell and the sound-emitting monomer resonate in the high frequency band, resulting in a downward peak in the frequency response curve and distorted sound of the sound-emitting device.
[0176] In summary, the shell of Comparative Example 1 is formed by injection molding of 70wt% PC material and 30wt% glass fiber. Although it can meet the requirements of structural strength, reliability, air tightness and waterproof, the density of PC material is relatively large, so it is difficult to meet the lightweight design requirements of the shell. The shell of Comparative Example 2 is formed by injection molding of 80wt% PA66 material and 20wt% glass fiber. Although it can meet the requirements of structural strength, high power reliability, etc., the PA66 material is a crystalline material, there is a phase interface, and the melting temperature is high, which affects its ultrasonic welding effect, so that there are cold welds and bubbles in its ultrasonic welding structure, and the ultrasonic welding is poor, so that it cannot meet the requirements of 10-meter waterproof test, high temperature and high humidity reliability test, and 2m drop test. And the density of the shell of Comparative Example 2 is relatively large, which does not meet the lightweight design requirements of the shell. The shell of Comparative Example 3 is formed by injection molding of 80wt% PP material and 20wt% glass fiber. The modulus of PP material is low, and the reinforcement effect of glass fiber on PP material is poor, resulting in a low bending modulus of the shell of Comparative Example 3. Since the dyne value on the surface of the PP material is too low, the UV adhesive relay is insufficient and the connection between the diaphragm and the shell is not firm. Therefore, the high temperature and high humidity reliability test, high power reliability test, 10m waterproof verification test, and 2m drop reliability test requirements of the shell are not met. The shell of Comparative Example 4 is formed by injection molding of 90wt% PP material and 10wt% glass fiber. The dyne value on the surface of the PP material is too low, which makes the UV adhesive relay insufficient, and the modulus of the PP material is low. The reinforcement effect of the glass fiber on the PP material is poor, resulting in a low bending modulus of the shell of Comparative Example 4. Due to the lower mass proportion of glass fiber, the rigidity of the shell of Comparative Example 4 is insufficient, and the bonding force between the diaphragm and the shell is insufficient. It failed the high temperature and humidity reliability test, high power reliability test, 10m waterproof verification test, and 2m drop reliability test.
[0177] The shells of Examples 1-9 are formed by injection molding of alloy material and carbon fiber material, the mass ratio of carbon fiber to the alloy material is 0.12-0.69, the melting temperature of the alloy material is low, the energy required for ultrasonic welding is lower, and welding is easier, thereby improving the welding firmness and airtightness between the first shell 10 and the second shell 40. Moreover, since the alloy material has the characteristic of low density, the density of the shell is 0.9g / cm 3 -1.25g / cm 3range, so that a lightweight design of the shell can be achieved. The melting temperature of the alloy material is low, which can make the shell have a small drop in strength during high-temperature operation and strong structural stability. Moreover, the above-mentioned composite material includes carbon fiber material, which has a high modulus and strength, thereby improving the structural strength of the shell. In addition, the bending modulus of the shell is in the range of 5GPa-35Gpa, which can not only avoid the resonance between the shell and the sound unit 20, but also reduce the processing difficulty of the shell, reduce shell defects, and improve product yield. The bending strength of the shell is in the range of 50MPa-350Mpa. When the shell is impacted, it is not easy to deform, and the processing difficulty of the shell is small, and the product yield is high. The thermal deformation temperature of the shell is ≥120℃, which makes the shell have strong high temperature resistance and is not easy to deform in high temperature and high humidity reliability and high power reliability verification.
[0178] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.
[0179] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.
Claims
1. A housing of a sound-generating device, characterized in that: The invention comprises a first shell and a second shell, wherein the first shell and the second shell are both provided with a welding portion, the welding portion of the first shell and the welding portion of the second shell are connected by ultrasonic welding, the welding portion is formed by injection molding of a composite material consisting of carbon fiber and alloy material, the mass ratio of the carbon fiber to the alloy material is 0.12-0.69, the alloy material comprises polypropylene and polyamide, and the mass ratio of the polyamide to the polypropylene in the alloy material is 0.1-0.
5.
2. The housing of the sound-generating device according to claim 1, characterized in that: The alloy material further includes a compatibilizer. In the alloy material, the content of the polypropylene is 60wt%-90wt%, the content of the polyamide is 9wt%-30wt%, and the content of the compatibilizer is 1wt%-10wt%.
3. The housing of the sound-generating device according to claim 2, characterized in that: The compatibilizer includes at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted polyethylene, ethylene acrylate copolymer, ethylene methacrylate copolymer, maleic anhydride grafted polystyrene, and maleic anhydride grafted EVA.
4. The housing of the sound-generating device according to claim 1, characterized in that: The polyamide includes at least one of long-chain polyamide and amorphous polyamide.
5. The housing of the sound-generating device according to claim 4, characterized in that: The long-chain polyamide includes at least one of PA610, PA612, PA1010, PA11, PA12, PA1212, PA1012, PA1111, PA1213, and PA1313; And / or, the melting enthalpy of the amorphous polyamide material is ≤5 J / g.
6. The housing of the sound-generating device according to claim 1, characterized in that: The composite material further comprises hollow glass microspheres, and the distribution density of the hollow glass microspheres in the composite material is 0.45 g / cm 3 -0.75g / cm 3 .
7. The housing of the sound-generating device according to claim 1, characterized in that: The carbon content of the carbon fiber is 90%-99.99%, and / or the graphitization degree R of the carbon fiber is 0.85-1.15, and / or the length of the carbon fiber is 0.1mm-1mm.
8. The housing of the sound-generating device according to claim 1, characterized in that: The carbon fiber is sizing treated with a sizing agent, and the sizing agent includes at least one of a polystyrene sizing agent, a polyamide sizing agent, a polyester sizing agent, and an epoxy resin sizing agent.
9. The housing of the sound-generating device according to claim 1, characterized in that: The entirety of at least one of the first shell and the second shell is a welded portion; or At least one of the first shell and the second shell includes a supporting portion, and the supporting portion is injection-moldedly connected to the welding portion.
10. The housing of the sound-generating device according to claim 9, characterized in that: The supporting portion includes a resin material, and the resin material includes at least one of PP, PA610, PA612, PA1010, PA11, PA12, PA1212, PA1012, PA1111, PA1213, PA1313, PPA, PA4T, PA6T, PA9T, PA10T, PA12T, PA46, ABS, PET, PBT, and PC.
11. The housing of the sound-generating device according to claim 10, characterized in that: The support part further comprises a fiber material, wherein the fiber material comprises carbon fiber and / or glass fiber, and the resin material is mixed with the fiber material, and a mass ratio of the fiber material to the resin material is 0.1-0.
7.
12. The housing of the sound-generating device according to claim 1, characterized in that: The density of the shell is 0.9 g / cm 3 -1.25g / cm 3 ; And / or, at least 10% of the area of the shell has a thickness of ≤0.3 mm.
13. The housing of the sound-generating device according to claim 1, characterized in that: The bending modulus of the shell is 5GPa-35GPa; And / or, the bending strength of the shell is 50MPa-350Mpa; And / or, the heat deformation temperature of the shell is ≥120°C.
14. The housing of the sound-generating device according to any one of claims 1 to 13, characterized in that: The surface tension of the shell is ≥36 dynes / cm; And / or, the housing has a waterproof rating of at least 1 ATM.
15. A sound-generating device, characterized in that: A housing comprising the sound emitting device according to any one of claims 1 to 14.
16. An electronic device, characterized in that: Comprising the sound-generating device as claimed in claim 15.
